2006
DOI: 10.1063/1.2358396
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental analysis of current spreading in AlGaInP light emitting diodes

Abstract: The profile of light emission from aluminum gallium indium phosphide ͑AlGaInP͒ light emitting diodes has been studied and compared with the theoretical modeling of current spreading using a lossy transmission line model of current injected into the active region. Discrepancies between the experimentally determined emission profile and the theoretically predicted current injected into the active region have been analyzed and explained using a Monte Carlo ray tracing simulation which considers the trajectories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As a matter of fact, it was shown that, in vertical LEDs, CC causes such negative effects on their performance, as it does in their lateral counterparts. Moreover, the recent studies suggest the existence of CC in AlGaInP LEDs [5], [9], [10]. Meanwhile, in all these researches, the impact of CC on the performance of vertical red LEDs grown on conductive substrates has not been reported in details in comparison to the avalanche of papers related to this effect in lateral blue InGaN LEDs grown on sapphire.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As a matter of fact, it was shown that, in vertical LEDs, CC causes such negative effects on their performance, as it does in their lateral counterparts. Moreover, the recent studies suggest the existence of CC in AlGaInP LEDs [5], [9], [10]. Meanwhile, in all these researches, the impact of CC on the performance of vertical red LEDs grown on conductive substrates has not been reported in details in comparison to the avalanche of papers related to this effect in lateral blue InGaN LEDs grown on sapphire.…”
Section: Introductionmentioning
confidence: 92%
“…Three types of devices with different p-contact shapes depicted as LED1, LED2, and LED3 were studied ( the emitting area. Such a contact shape is typical of commercial devices and traditionally has been a model for studies of the CC [5], [9]. The LED2 and LED3 1 1 mm in size had circular p-contacts 100 m in diameter and four crossed 30-m-wide contact stripes.…”
Section: Device Designmentioning
confidence: 99%
“…In most cases, shortcomings are related to the removal of heat, 3 which is due to the JH of the structure and increased rate of nonradiative Auger recombination of injected charge carriers. In our opinion, the appearance of the current crowding ͑CC͒ effect, 4 which is rarely mentioned in AlGaAs/GaAs structures 5 but is well established in less efficient blueshifted [6][7][8] and redshifted [9][10][11][12] LEDs, should also be considered. This effect is due to the localization of the current flow rout in some regions of a multilayer LED structure whose position and geometry are difficult to predict a priori.…”
Section: Introductionmentioning
confidence: 99%
“…The current crowding effect is well known in LEDs operating in both visible (based on InGaN [1] and AlGaInP [2]) and IR (InAsSb [3]) spectral intervals. Several investigations have been devoted to numerical simulation [4,5] and analytical modeling [1,6,7] of current spreading in LEDs. These works were aimed at improvement of current spreading in the active region of devices through optimization of the internal param eters (resistance and thickness of the substrate, con finement layers, and current spreading layers) and the geometry of contacts.…”
mentioning
confidence: 99%